"Human Error" Isn't Enough. Marine Accident Evaluation Methods: A Systematic Review. (September 2021) - Ward, Alexandria D.; Nathan-Roberts, Dan
The commercial shipping industry continues to be responsible for a vast majority of the world's trade, yet it remains behind similar transport industries in terms of safety and accident prevention. The regulation of safety systems and naval architecture have led to significantly fewer accidents, but human error remains a constant factor and has been identified as the most likely cause of a marine accident. A systematic review of the methods used to investigate latent factors regarding human error in marine accidents has been conducted in an effort to further examine casual factors which lead to human error. Widely accepted methods or modified methods from other high-risk industries such as Human Factors Analysis and Classification System (HFACS) and Bayesian Networks have been utilized, but few have taken into account all of the sociotechnical macroergonomics of such a complex industry, leaving significant research and engineering potential.